Bibliography of the Works on Jelena Balšić (between 1366 and 1371–1443) (Knjiženstvo, journal for studies in literature, gender and culture, 2023)
This bibliography includes articles, studies and books that are dedicated to an important figure of the fifteenth-century Serbian culture – a ruler and writer Helen Balšić. The novels, plays and other non-scientific writings dealing with her life are also listed. Editions of her works – letters, contract with Venice, ktitor inscription and testament – are noted as well. Even the texts in which she is only mentioned are taken into account. The order is chronological.
Keywords: Bibliography; Serbia; fifteenth century; woman ruler; epistolography